Translating knowledge in the multilingual paradigm - Bennett, Karen (2023)
The term ‘epistemicide’ was first coined by the Portuguese sociologist, Boaventura de Sousa Santos to refer to the systematic eradication by western science of the indigenous knowledges of the Global South. It was later applied to translation by Bennett in order to describe the way that academic texts produced in non-Anglophone cultures often have to be so radically rewritten for publication in international journals that their epistemological infrastructure is effectively destroyed. The long-term consequences of this process included, it was argued, a drift toward an epistemological monoculture, as scholarly discourses in other languages assimilated to the dominant one through a process of calquing. This argument was developed at a time when the hegemony of English appeared unassailable in the world of academic publishing and beyond. Since then, however, the multi- or translingual paradigm has profoundly challenged this assumption. This article focuses on how knowledge is generated and disseminated within this new paradigm and its implications for Translation Studies. Considering the prevalence, in this domain, of second-language writing, self-translation and paratranslational activities (like language revision and editing), and the demands of a readership with multilingual competence, it suggests that a much broader concept of translation might now be in order.